2014
DOI: 10.1007/s40477-014-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

In-continuity neuroma of the median nerve after surgical release for carpal tunnel syndrome: case report

Abstract: Iatrogenic injuries of the median nerve after surgical release for carpal tunnel syndrome resulting in the formation of a neuroma are rare. We present here the case of two patients, one with a bifid median nerve, showing in-continuity neuroma after surgical release for carpal tunnel syndrome. The patients reported persistent post-operative pain and showing symptoms. In both cases, ultrasound showed an in-continuity neuroma with a hypoechoic and enlarged median nerve at the carpal tunnel. The case report shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Neuroma formation from injury to one of these branches may also contribute to scar hypersensitivity. 42,43 Both endoscopic and open approaches may be used for CTR. 38e41 The length of the incision varies, but often it is less than 4 cm and limited to the palm.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroma formation from injury to one of these branches may also contribute to scar hypersensitivity. 42,43 Both endoscopic and open approaches may be used for CTR. 38e41 The length of the incision varies, but often it is less than 4 cm and limited to the palm.…”
Section: Discussionmentioning
confidence: 99%
“…Depaoli et al reported two patients with CTS who still had local pain and paresthesia after decompression surgery. Ultrasound examination showed that there was a schwannoma related to the median nerve in the carpal canal, and the patients’ symptoms were relieved after surgical resection ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…[11] In another case, they reported a neuroma following the median nerve injury after operation. [12] Disclosures Informed Consent: Written informed consent was obtained from the patient who participated in this study. …”
Section: Discussionmentioning
confidence: 99%